Juridical Review On The Crime Of Driving Negligence That Caused Other People's Death (Analysis Of Judge's Decision Number 20/Pid.B/2018/Pn.Mna) - Asep Aidul Adha; Widya Timur; Ferawati Royanti (Fakultas Hukum Dehasen, 2022)
The high rate of traffic accidents (lakalantas) itself occurs due to a lack of public awareness in this case motorized vehicle drivers with various factors attached to themselves, for example in terms of physical fitness, mental readiness when the driver is tired, the influence of alcohol and illegal drugs. This thesis examines the application of material criminal law to the crime of negligence in driving which causes the death of a person and the judge's legal considerations in making a decision on the offense of negligence in driving that causes the death of a person in case Number 20/Pid.B/2018/PN.Mna. The legal research method used is normative legal research or library research. This is research that examines document studies, using various secondary data such as legislation, court decisions, legal theory, and can be in the form of opinions of scholars. The results of the research in this case, are the Panel of Judges using a single indictment, namely Article 310 paragraph (4) of the Republic of Indonesia Law no. 22 of 2009 concerning Road Traffic and Transportation where the elements in the indictment have been deemed proven by the Panel of Judges. Where, between the actions and the elements of the article match each other. The Panel of Judges complies with the applicable law, which is based on at least two valid pieces of evidence, where in this case, the evidence used by the judge is witness testimony, evidence, visum et repertum and statement of the defendant.